2020
DOI: 10.22405/2226-8383-2020-21-3-84-88
|View full text |Cite
|
Sign up to set email alerts
|

Representing Matrices over Fields as Square-Zero Matrices and Diagonal Matrices

Abstract: Представление матриц над полями в виде матриц с нулевым квадратом и диагональных матриц П. Данчев Пётр Данчев -доктор математики, Институт математики и информатики Болгарской академии наук (г. София, Болгария).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Let us consider below two situations, namely, algebraically closed fields (see Corollary 2.4) and finite fields (see Corollary 3.2). The results can be viewed and treated as the development of method and ideas presented in [8] and [6], respectively. Some closely related studies can also be found in [5].…”
Section: Introduction and Conventionsmentioning
confidence: 99%
“…Let us consider below two situations, namely, algebraically closed fields (see Corollary 2.4) and finite fields (see Corollary 3.2). The results can be viewed and treated as the development of method and ideas presented in [8] and [6], respectively. Some closely related studies can also be found in [5].…”
Section: Introduction and Conventionsmentioning
confidence: 99%